Long non-coding RNA OIP5-AS1 suppresses microRNA-92a to augment proliferation and metastasis of ovarian cancer cells through upregulating ITGA6 - Yujue Wang; Lingling Li; Xun Zhang; Xiaolan Zhao (BMC, 2022)
Abstract Objective Recently, long non-coding RNAs (lncRNAs) and microRNAs (miRNAs) have been identified as essential biomarkers during development of malignancies. This study was performed to study the roles of lncRNA opa-interacting protein 5 antisense transcript 1 (OIP5-AS1) and miR-92a in ovarian cancer (OC). Methods OIP5-AS1, miR-92a and integrin alpha 6 (ITGA6) expression in OC tissues and cells was assessed. The screened OC cells were respectively with OIP5-AS1-, miR-92a- and ITGA6-related vectors or oligonucleotides . The viability, migration, invasion and apoptosis of the cells were determined and the levels of epithelial-mesenchymal transition (EMT)-related proteins were also measured. The interactions between OIP5-AS1 and miR-92a, and between miR-92a and ITGA6 were confirmed. Results OIP5-AS1 and ITGA6 were upregulated while miR-92a was downregulated in OC. Inhibited OIP5-AS1 or downregulated ITGA6 or elevated miR-92a repressed EMT, viability, migration and invasion, and promoted apoptosis of OC cells. OIP5-AS1 as a competing endogenous RNA interacted with miR-92a to regulate ITGA6. These effects that induced by silenced OIP5-AS1 could be reversed by miR-92a inhibition while those that induced by up-regulated miR-92a were reduced by restored ITGA6. Conclusion OIP5-AS1 silencing promoted miR-92a to repress proliferation and metastasis of OC cells through inhibiting ITGA6.